Highly Porous Magnesium Alloy Structures and Their Properties Regarding Degradable Implant Application1. Issue 3 (11th November 2013) - Morgenthal, Ingrid; Andersen, Olaf; Kostmann, Cris; Stephani, Günter; Studnitzky, Thomas; Witte, Frank; Kieback, Bernd; Stephani, Günter; Scheffler, Michael
<x xml:space="preserve">Abstract</x> Magnesium alloys offer excellent properties with regard to application as degradable implant. For bone implants, it is often desirable to use porous materials. However, the preparation of high‐porosity magnesium implants has been difficult so far. The present study uses melt extracted magnesium fibers as the starting material for the sintering of highly porous magnesium bodies, i.e., from alloys MgY4 (W4) and MgY2Zn1CaMn (WZ21). Single short fibers of these alloys with an equivalent diameter between 100 and 250 µm and a length of 4–8 mm are manufactured by melt extraction. Thermodynamic calculations are used to determine the best conditions for liquid phase sintering of these Mg alloys. As no organic or other substances are needed in the process, it is possible to obtain high‐purity, high‐porosity (up to 75%) bodies with exclusively open porosity. Metallographic studies as well as mechanical and corrosion testing experiments complete this work.